Evaluation of Poverty Reduction Programs in Batam City - Bobby Mandala Putra; Azhar Abbas (Indonesian Association for Public Administration (IAPA), 2019)
Poverty is still a severe problem in Indonesia. Statistics show that until the end of 2017, the number of poor people in Indonesia is 26.58 million people or 10.12 percent of the total population. Uniquely, when the poverty rate has decreased in various regions in Indonesia, the poverty rate in Batam has increased. At present, the number of poor people in Batam City is 28,674 families. Although there is a reasonably high interest in poverty, the amount of research in Batam is still limited. The purpose of this study is to describe and analyze poverty reduction programs in Batam City. This research was conducted using qualitative descriptive research. The research proves that the poverty reduction program in Batam City has five impacts on public problems: first, the poverty reduction program has not been able to reduce poverty; second, the target group feels that their lives are better after receiving a poverty reduction program; third, the target group continues to live in poverty; fourth, the target group feels that the state is present in their lives; fifth, the target group has resigned to living in poverty. Besides, poverty reduction programs have two effects on the spillover effect; first, the emergence of social jealousy in the community; second, increase incumbent electability. In closing, this study recommends that poverty reduction programs still need to be continued but need to be revised. The improvement is to provide education and stimulation to recipients of poverty reduction programs so that they can escape poverty.